Add the expressions.

Expression 1: −3k+4k3−2

Expression 2: 9k2−3k3+4k−3

(2 points)
k3+
k2+
k+

1 answer

To add the expressions −3k+4k^3−2 and 9k^2−3k^3+4k−3, we combine like terms.

First, let's combine all the terms with k^3: -3k^3 + 4k^3 = k^3.

Next, let's combine all the terms with k^2: 0k^2 + 9k^2 = 9k^2.

Now, let's combine all the terms with k: -3k + 4k = k.

Finally, let's combine the constants: -2 + (-3) = -5.

Putting it all together, we have the simplified expression:

k^3 + 9k^2 + k - 5.